2019
DOI: 10.1002/ese3.367
|View full text |Cite
|
Sign up to set email alerts
|

Private‐sector partner selection for public‐private partnership projects of electric vehicle charging infrastructure

Abstract: Public‐private partnership (PPP) models, which can mitigate the deflection of charging facilities, have been introduced for electric vehicle charging infrastructure (EVCI) projects. Private‐sector partner selection is a significant step to ensure the success of EVCI‐PPP projects, but it has been rarely studied. This paper therefore identifies selection criteria for private partners in EVCI‐PPP projects and assesses the alternatives using an extended multicriteria operation and compromise solution (VIKOR) metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 54 publications
(63 reference statements)
0
17
0
7
Order By: Relevance
“…They play an important role in the policy agenda and are an important method of political socialization. The "focus effect" of news reports is expectant with the huge pressure of public opinion which urges local governments to pay attention to public demand and achieve the goal of decision-making democratization [41][42][43]. Previous studies have shown that news reports play an important role in the policy diffusion of examples such as a public bicycle program [42,44], local government performance evaluation [37], and government purchase of public services [43,45] and in other fields [44,46].…”
Section: Hypothesis 6 (H6)mentioning
confidence: 99%
“…They play an important role in the policy agenda and are an important method of political socialization. The "focus effect" of news reports is expectant with the huge pressure of public opinion which urges local governments to pay attention to public demand and achieve the goal of decision-making democratization [41][42][43]. Previous studies have shown that news reports play an important role in the policy diffusion of examples such as a public bicycle program [42,44], local government performance evaluation [37], and government purchase of public services [43,45] and in other fields [44,46].…”
Section: Hypothesis 6 (H6)mentioning
confidence: 99%
“…A similar conclusion was reached in Canada [58] and Europe [59], and other areas as summarized in Table 3. [61].…”
Section: Phase 1 Coordination Modementioning
confidence: 99%
“…For this reason, Gürbüz et al (2012) presented an integrated MCDM method to select the ERP problem with a conflict criterion. Zhang et al (2019) proposed the private-sector partner selection for the public-private partnership (3P) charging electric vehicles infrastructure problem. The study used the extended Vlse Kriterijumska Optimizacija Kompromisno Resenje (VIKOR) method under the IFS condition.…”
Section: Introductionmentioning
confidence: 99%